Minat Siswa dalam Pembelajaran Penjas pada Masa Pandemi Covid-19 di SMPN 1 Telukjambe Barat Karawang - Yusril Arfah Setiawan; Abduloh Abduloh; H. Nana Suryana Nasution (Peneliti.net, 2021)
This study aims to determine student interest in learning physical education during the COVID-19 pandemic at SMPN 1 Telukjambe Barat Karawang. The research method uses a survey method with a questionnaire or questionnaire in the google form. Based on the results of the study, it can be concluded that students' interest in learning physical education during the covid-19 pandemic at SMPN 1 Telukjambe Barat Karawang was in the